Interspecific Variation in Seasonal Migration and Brumation Behavior in Two Closely Related Species of Treefrogs - Borzée, Amaël; Choi, Yoojin; Kim, Ye Eun; Jablonski, Piotr G.; Jang, Yikweon (Frontiers in Ecology and Evolution, 2019)
Most amphibians migrate between flooded habitats for breeding and dry habitats for non-breeding activities, however, differences in closely related species may highlight divergent evolutionary histories. Through field surveys, Harmonic Direction Finder tracking and laboratory behavioural experiments during the wintering season, we demonstrated differences in seasonal migration and hibernation habitats between Dryophytes suweonensis and D. japonicus. We found that D. japonicus migrated towards forests for overwintering and then back to rice paddies for breeding in spring. By contrast, D. suweonensis was found to hibernate buried in the vicinity of rice paddies, its breeding habitat. We also found that the difference in migrating behaviour matched with variation in microhabitat use during brumation and hibernation between the two species. Our findings highlight different ecological requirements between the two species, which may result from their segregated evolutionary histories, with speciation potentially linked to species use of a new breeding habitat. Additionally, the use of rice paddies for both breeding and hibernation may contribute to the endangered status of D. suweonensis because of the degradation of hibernation sites in winter.